The physical and genetic map of mtDNA from Neurospora crassa strain 74-OR23-1A. - R. A. Collins; D. M. Grant; A. M. Lambowitz (Fungal Genetics Reports, 1982)
The physical and genetic map of mtDNA from Neurospora crassa strain 74-ORS23-1A.